MICROBIAL BIOCONVERSION TO PRODUCE NUTRACEUTICAL AND PHARMACEUTICAL BIOACTIVE COMPOUNDS - Siti Mahyuni (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
The bioconversions of bioactive health supporting compounds using certain microorganisms have long been known, however it has not been widely applied in industrial scale to produce nutraceutical and products of high economic value. This review article will discuss the group of steroids, carotenoids and statins which were produced by microbial bioconversion using the various substrates and conditions. The information presented in this article were collected from scientific books and articles in national and international journals which can be validated and traced back to their sources through many sites such as google.com, google scholar, NCBI and Science Direct. From the information compiled in this article, it can be concluded that the bioconversion of bioactive compounds by microorganisms has shown positive results and potential to be further optimized and applied in an industrial scale to produce natural bioactive compounds as basic ingredients for nutraceutical and pharmaceutical products with high economic value. Senyawa-senyawa bioaktif penunjang kesehatan hasil biokonversi oleh mikroorganisma telah lama dikenal namun dimanfaatkan secara maksimal pada industri nutraseutik dan farmaseutik untuk menghasilkan produk-produk bernilai ekonomi tinggi. Pada artikel ini akan ditinjau produk-produk nutraseutikal dan farmaseutikal dari golongan steroid, golongan karetinoid, dan golongan statin yang dihasilkan dari proses biokonversi oleh berbagai mikroorganime. Informasi-informasi yang disajikan didapatkan dengan metoda studi lieratur mengacu pada berbagai tulisan ilmiah nasional dan internasuonal yang dapat divalidasi dan dilacak kembali sumbernya melalui situs-situs google.com, google scholar, NCBI dan Science Direct. Dari artikel tinjauan ini dapat disimpulkan bahwa biokonversi senyawa bioaktif oleh mikroorganisma menunjukkan hasil-hasil positif dan berpotensi untuk dioptimasi dan diterapkan lebih lanjut pada skala industri untuk menghasilkan senyawa-senyawa sebagai bahan dasar produk nutraseutik dan farmasetik yang bernilai ekonomi tinggi.